UNLOCKING CREATIVITY WITH PADLET: A DIGITAL COLLABORATION TOOL (Journal of Universal Science Research, 2025)
This study investigates the impact of Padlet, a digital collaboration tool, on fostering creativity in various collaborative contexts. By examining its key features, applications, and user engagement, this paper aims to explore how Padlet can enhance creative workflows across education, business, and community development. Findings highlight the tool's ability to facilitate interactive, multimedia-rich collaboration, despite some limitations. This research underscores the potential of digital tools like Padlet in unlocking creativity and supporting collaborative processes.